Tenogenic Induction From Induced Pluripotent Stem Cells Unveils the Trajectory Towards Tenocyte Differentiation - Yoshimoto, Yuki; Uezumi, Akiyoshi; Ikemoto-Uezumi, Madoka; Tanaka, Kaori; Yu, Xinyi; Kurosawa, Tamaki; Yambe, Shinsei; Maehara, Kazumitsu; Ohkawa, Yasuyuki; Sotomaru, Yusuke; Shukunami, Chisa (Frontiers in Cell and Developmental Biology, 2022)
The musculoskeletal system is integrated by tendons that are characterized by the expression of scleraxis (Scx), a functionally important transcription factor. Here, we newly developed a tenocyte induction method using induced pluripotent stem cells established from ScxGFP transgenic mice by monitoring fluorescence, which reflects a dynamic differentiation process. Among several developmentally relevant factors, transforming growth factor-beta 2 (TGF-b2) was the most potent inducer for differentiation of tenomodulin-expressing mature tenocytes. Single-cell RNA sequencing (scRNA-seq) revealed 11 distinct clusters, including mature tenocyte population and tenogenic differentiation trajectory, which recapitulated the in vivo developmental process. Analysis of the scRNA-seq dataset highlighted the importance of retinoic acid (RA) as a regulatory pathway of tenogenic differentiation. RA signaling was shown to have inhibitory effects on entheseal chondrogenic differentiation as well as TGF-b2-dependent tenogenic/fibrochondrogenic differentiation. The collective findings provide a new opportunity for tendon research and further insight into the mechanistic understanding of the differentiation pathway to a tenogenic fate.